EFFECT OF ANTI-OXIDANT SUPPLEMENTATION ON POST THAW SPERM CHARACTERISTICS, CELLULAR ENZYME LEAKAGE AND LIPID PEROXIDATION IN BULL SEMEN - RAO, M MUTHA; VERMA, PAWAN KUMAR; BHAT, MUZAFER AHMED; PANDEY, A K; RAINA, R (The Indian Journal of Animal Reproduction, 2023)
A study was conducted to assess the influence of na,Jral (Vitamin E) and synthetic (Butylated HydroxylToluene; BHT) anti-oxidants on post-thaw semen characteristics, enzyme release (lactic dehydrogenase. acidphosphatase and cholinesterase) into extra cellular medium and lipid peroxidation following freezing and thawingin crossbred HF bulls. Semen was collected from three crossbred bulls (HFxT) twice a week and a total of 18collections (six collections per bull) were utilized in this study. After initial evaluation each semen sample wassplit into three equal fractions and diluted in tris egg yolk extender containing either vitamin E 0.3mg/ml (TEY-E),BHT 2.0mM (TEY-B) or with out any additive (TEY-C) which acted as control. Filling and sealing of individualdiluted semen samples in PVA straws, equilibration at 4 °C for 4h, freezing in programmable freezer and plungingof straws into liquid nitrogen were followed as per standard procedure. Thawing of semen was performed at 37°Cfor 30 seconds. Post-thaw semen characteristics such as progressive motilitv live sperm(%), and acrosomalintegrity (%) were significantly higher and sperm abnormalities were significantly lower in samples containingVit.E and BHT over the control. The leakage of enzymes (IU/L) such as acid phosphatase, cholinesterase andlactic dehydrogenase was significantly lo,wer in TEY-E followed by TEY-B and highest in the TEY-C diluents. TheMDA levels (umol/ml) increased significantly in non-antioxidant added samples (0.60 ± 0.05) over Vit.E (0.11 ±0.01) and BHT (0.19 ± 0.02) containing samples following thawing. The results revealed that supplementation ofVit.E and BHT to tris egg yolk extender improved the post-thaw semen quality in bulls.
Keywords: Cellular enzyme; Bull semen